PRIBUMISASI ISLAM NUSANTARA: ANTARA NALAR BERAGAMA DAN GERAKAN SOSIAL KEAGAMAAN DI INDONESIA - Arik Dwijayanto (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2017)
This study aims to explore the values ​​of Islamic Nusantara as the reason of religiousity and spirit of religious-social movement in Indonesia. Islam Nusantara in its development comes as social-religious movement for moderate society to maintain the existence of tolerant Islamic teachings. Through the historical-sociological approach, the results of this research show the fact that there are four factors that encourage the indigenous Islamic Nusantara emerged as a social movement in Indonesia. Firstly, the historical fact of the santri-kyai's contribution through the Jihad Revolution in defending independence has reinforced that there is no dichotomy between religious teachings and nationalism. Secondly, as a result of the internalization of the value of character education through “pesantren” and “madrasah” that has proven to be a stronghold in the face of religious radicalism. Thirdly, as a continuation of the ideas of the predecessors (moslem scholars) to present a friendly, tolerant and peaceful of Islamic doctrine. Fourthly, as the realization of the responsibility of religious organizations that rely on the understanding of Islamic teachings based the value of Ahlussunnah waljamaah.